Magnetic, Phonon and Optical Properties of Transition Metal and Rare Earth Ion Doped ZnS Nanoparticles - Iliana Apostolova; Angel Apostolov; Julia Wesselinowa (Nanomaterials, 2022)
The surface, size and ion doping effects on the magnetic, phonon and optical properties of ZnS nanoparticles are studied based on the s-d model including spin-phonon and Coulomb interaction, and using a Green’s function theory. The changes of the properties are explained on a microscopic level, due to the different radii between the doping and host ions, which cause different strains—compressive or tensile, and change the exchange interaction constants in our model. The magnetization increases with increasing small transition metal (TM) and rare earth (RE) doping concentration. For larger TM dopants the magnetization decreases. The phonon energies increase with increasing TM, whereas they decrease by RE ions. The phonon damping increases for all doping ions. The changes of the band gap energy with different ion doping concentration is also studied. Band gap changes in doped semiconductors could be due as a result of exchange, s-d, Coulomb and electron-phonon interactions. We have tried to clarify the discrepancies which are reported in the literature in the magnetization and the band gap energy.